2010
DOI: 10.1111/j.1439-0426.2010.01436.x
|View full text |Cite
|
Sign up to set email alerts
|

MMP-13(Matrix MetalloProteinase 13) expression might be an indicator for increased ECM remodeling and early signs of vertebral compression in farmed Atlantic salmon (Salmo salarL.)

Abstract: SummaryVertebral body compression is a common problem in commercial farming of Atlantic salmon. Although risk factors, such as vaccination and malnutrition, have been identified, the etiology is largely unknown. Histological studies of Atlantic salmon have shown that in a compressed deformity (platyspondyly) the length of the compact bone is reduced while the notochord start to form atypical chrondrogenic structures. In mammals, similar remodeling activities have been linked to inflammatory processes in the ti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(18 citation statements)
references
References 21 publications
0
18
0
Order By: Relevance
“…The process underlying temperature‐induced anomalies in salmon is only hypothesized by Wargelius et al . (): in fish reared at higher temperature, in the compressed vertebrae, notochord, compact and trabecular bone, MMP13 was significantly upregulated, 44 weeks after seawater transfer. Ytteborg et al .…”
Section: Causative Factors Of Skeletal Anomalies In Reared Fishmentioning
confidence: 90%
See 1 more Smart Citation
“…The process underlying temperature‐induced anomalies in salmon is only hypothesized by Wargelius et al . (): in fish reared at higher temperature, in the compressed vertebrae, notochord, compact and trabecular bone, MMP13 was significantly upregulated, 44 weeks after seawater transfer. Ytteborg et al .…”
Section: Causative Factors Of Skeletal Anomalies In Reared Fishmentioning
confidence: 90%
“…Among the main risk factors invoked for the onset of spinal anomalies, in contrast to those reported in non‐salmonid species, temperature seems to be the most potent (Wargelius et al . ), together with smoltification timing (underyearlings instead of yearlings), vaccination and dietary phosphorus deficiency, even if the reproducibility of induction of these anomalies by these factors has not always succeeded in laboratory conditions (Gil Martens ).…”
Section: Vertebral Column Anomaliesmentioning
confidence: 99%
“…This shows that regular mechanical load has a positive effect on bone development, as reported for cichlids (Huysseune et al., 1994) and for mammals (Boyde, 2003). Wargelius et al. (2010a) found that a group of postsmolts with a high mRNA expression level in vertebral bone of MMP‐13 (Matrix MetalloProteinase 13), which codes for a protein belonging to a family of proteins involved in the degradation of the extracellular matrix, developed a high percentage of fish with compressions later on.…”
Section: Causes and Pathogenesis Of Vertebral Deformitiesmentioning
confidence: 99%
“…The aggravation of deformities involves the increase of the number of deformed vertebral bodies adjacent to an already existing location of malformed and fused vertebral bodies (Witten et al., 2006; Fjelldal et al., 2007a). There appears to be a delay of several weeks between the induction and the development of a deformity (Wargelius et al., 2010a; Grini et al., 2011). The expression level of several genes is different in deformed compared to normal vertebrae; collagen type XI a1 gene is down‐regulated in the compact but not in the trabecular bone (Wargelius et al., 2010b) and MMP‐13 is up‐regulated in both compact and trabecular bone of compressed vertebrae (Wargelius et al., 2010b).…”
Section: Causes and Pathogenesis Of Vertebral Deformitiesmentioning
confidence: 99%
“…However, cellular and molecular events during pathological bone development in salmon have been little described and only a few studies have been published (e.g. Wargelius et al., 2010a,b; Ytteborg et al., 2010a,b,c). Our group recently finished a comprehensive study on temperature induced vertebral fusions in Atlantic salmon, where we described various stages of pathological development using molecular tools.…”
Section: Introductionmentioning
confidence: 99%